Pengaruh Media Pembelajaran Kartu Huruf Terhadap Keterampilan Membaca pada Siswa Kelas I Pembelajaran Bahasa Indonesia di SDN Joglo No. 76 Surakarta Tahun 2025 - Hanifah Dwi Yuniarti; Anita Trisiana; Jumanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study focuses on determining whether the use of letter card learning media has an effect on the reading skills of grade I students in Indonesian language at SD N Joglo No. 76 Surakarta in 2025. This quantitative investigation applied a Quasi-Experimental Design in the form of a Pretest-Posttest Control Group Design. All grade I students at SD N Joglo 76 Surakarta in the 2025 academic year served as the population in this study. The sampling method used was total sampling, with 27 grade IA students as participants. The information gathering process involved observation, documentation, and testing. The analysis of the research data revealed a hypothesis test result with a calculated t-value of 5.104. The t-table value at 26 degrees of freedom (i.e., 27-1) and a significance level of 5% was 2.056. The normality test results showed that the calculated t-value (5.104) exceeded the t-table value (2.056), thus Ha was accepted and Ho was rejected. This research also found a change in the average student interest in learning from 65.07 (at the initial stage) to 81.63 (at the final stage). Therefore, it can be concluded that letter cards as a learning medium impacted the reading skills of first-grade students in Indonesian language learning at SD N Joglo No. 76 Surakarta in 2025.